Mind your language: Explaining the retreat of the Irish language frontier - Alan Fernihough; Christopher L. Colvin; Eoin McLaughlin (Queen's University Centre for Economic History (QUCEH), 2024)
Why do we choose one language over another? Rival views see language frontiers as exogenous, driven by policy, or endogenous, determined by social, cultural and economic forces. We study language loss in nineteenth-century Ireland's bilingual society using individual-level data from the 1901 census. Our analysis highlights the intergenerational influence of the education received by a community's elders on subsequent generations' language use. This is consistent with an endogenous demand for English driving language choice because the elder generation's literacy was acquired by attending privately financed voluntary primary schools in a period that predates state-funded compulsory schooling.
Keywords: I24; I28; N33; N93; R12; Z13; 330; language loss; bilingualism; education policy; census data; Ireland